Analisis Faktor-Faktor yang Mendorong Konsumen Berbelanja di Shopee - Anisa Dwi Kiswati; Arpidah Ayu Syafitri; Hidayah Nabila Asnur; Yenni Samri Juliati Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Digital transformation (digitization) has penetrated almost all lines of people's lives, one of which is trade activities. Trading activities in this digital era are expressed by the emergence of e- commerce, one of which is Shopee. Shopee as an e-commerce in Indonesia does not stand alone, but there are other e-commerce that compete to dominate digital trading activities. Intense competition makes every e-commerce company compete to create features and services that are effective, efficient and make it easier to increase consumer transaction numbers. This research aims to find out what factors encourage consumers to shop at Shopee. The approach method used in this research is a quantitative approach involving 30 respondents who filled out a Google Form questionnaire which was distributed to Shopee users. The results of this research show that there are several factors that encourage consumers to shop at Shopee, these factors are social influence, offers and promotions, ease of access, price, trust and security, reviews and ratings, product quality, benefits of shopping at Shopee and service factor.